Imago - Rhian Parker (Hyperrhiz, 2022)
“Imago” is a poem birthed from a place of understanding surrender. More specifically; the poem is an empathetic effort to understand the choices of one’s parents from the position of an adult child. The collages work with the extended metaphor of “a fly in your glass of wine” while also presenting the ever-Southern aftermath of a drink left outside, right underneath the porch lights.